Gall bladder torsion: a disease of the elderly. Issue 10 (23rd October 2019) - David, Rowan; Traeger, Luke; McDonald, Christopher
Abstract : We describe the case of a gall bladder torsion in an elderly female patient, which was discovered during laparoscopic exploration for presumed acute cholecystitis. The rising incidence of this relatively uncommon process can be attributed to increasing life expectancy. Gall bladder torsion typically manifests in septuagenarians and octogenarians of the female gender, as seen in the presented case. It is thought that local mesenteric redundancy predisposes to the development of mechanical organoaxial torsion along the gall bladder's longitudinal axis involving the cystic duct and artery. Clinicians must have a high index of suspicion for gall bladder torsion, as a mimicker of acute cholecystitis, in the described patient demographic. Preoperative diagnosis is challenging with the vast majority of reported cases being diagnosed intraoperatively, and only five cases preoperatively. Prompt surgical intervention results in an overall mortality rate of approximately 5%, while a delay in diagnosis can lead to catastrophic patient outcomes.